2009
DOI: 10.1126/science.1178158
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequence, Comparative Analysis, and Population Genetics of the Domestic Horse

Abstract: We report a high-quality draft sequence of the genome of the horse (Equus caballus). The genome is relatively repetitive, but has little segmental duplication. Chromosomes appear to have undergone few historical rearrangements – 48% of equine chromosomes show conserved synteny to a single human chromosome. Equine chromosome 11 is shown to have an evolutionary novel centromere devoid of centromeric satellite DNA, suggesting that centromeric function may arise prior to satellite repeat accumulation. Linkage dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
682
7
13

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 708 publications
(732 citation statements)
references
References 18 publications
24
682
7
13
Order By: Relevance
“…This may be a result of the difficulty of calling repeats with high similarity from shortread sequencing data 23 . However, the general distribution patterns of transposable element classes across chromosomes are similar to that of other assembled mammalian genomes 24,25 (Supplementary Fig. 8).…”
Section: Repetitive Sequences and Transposable Elementssupporting
confidence: 61%
“…This may be a result of the difficulty of calling repeats with high similarity from shortread sequencing data 23 . However, the general distribution patterns of transposable element classes across chromosomes are similar to that of other assembled mammalian genomes 24,25 (Supplementary Fig. 8).…”
Section: Repetitive Sequences and Transposable Elementssupporting
confidence: 61%
“…For example, in the Hanoverian Warmblood, N e was estimated to be 372 (Hamann and Distl, 2008). Wade et al (2009) found unusually high LD in Thoroughbreds compared with other horse breeds. Nevertheless, GS should be feasible, because strength of LD across several horse breeds (Wade et al, 2009) is comparable to LD in Holstein cattle (Qanbari et al, 2010), where GS was implemented successfully.…”
Section: Resultsmentioning
confidence: 99%
“…The availability of 50-K SNP chip technology, as well as the recent release of the horse genome sequence (Wade et al, 2009), provides the framework to estimate highly reliable GEBVs analogous to dairy cattle (e.g. VanRaden et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Genome‐wide association studies (GWASs) rapidly gained popularity after the sequencing of the genomes of several animal species, including human beings 31, 32, 33, 34. The completion of the sequencing and assembly of these reference genomes (an assembly of the DNA sequence and its chromosomal locations representing the genetic baseline of a species) provided a tool that could be used as a map indicating where elements of the genome reside.…”
Section: Genome‐wide Association Studiesmentioning
confidence: 99%
“…The resultant scatter plots are known as Manhattan plots because they resemble the skyline of a major city with some points that tower over the majority of others. Determining the genome sequence of the domestic horse led to the development of 2 equine SNP arrays that could be used for GWAS by researchers 32, 39…”
Section: Genome‐wide Association Studiesmentioning
confidence: 99%